Prospective comparison of breast pain in patients participating in a randomized trial of breast-conserving surgery and tamoxifen with or without radiotherapy. - Rayan, G; Dawson, L; Bezjak, A; Lau, A; Fyles, A; Yi, Q; Merante, P; Vallis, K (2003)
PURPOSE: To determine whether breast pain affects quality of life (QOL) after breast-conserving surgery and tamoxifen (TAM) with or without adjuvant breast radiotherapy (RT). METHODS AND MATERIALS: A randomized clinical trial was carried out at the Princess Margaret Hospital between 1992 and 2000 to evaluate the need for breast RT in addition to TAM in women >or=50 years treated with breast-conserving surgery for T1-T2N0 breast cancer. A companion study to assess breast pain was carried out during the last 2 years of the randomized clinical trial. The short-form McGill Pain Questionnaire (SF-MPQ), the European Organization for Research and Treatment of Cancer (EORTC) QOL (QLQ-C30) and EORTC breast cancer module (QLQ-BR23) questionnaires were completed by patients within 1 week of randomization in the randomized clinical trial (baseline) and at 3, 6, and 12 months. RESULTS: Eighty-six patients participated in the breast pain study; 41 received RT plus TAM and 45 received TAM alone. The median age was 70 years (range 51-80). The baseline pain and QOL scores were similar for the two groups. No significant difference was found between the two groups for each scale of the QLQ-C30 and QLQ-BR23 questionnaires at 3, 6, or 12 months (p >0.100), except that at 12 months, the score for role function (QLQ-C30) was higher in the RT plus TAM group than in the RT-only group (p = 0.02). At 3 months, the difference between the mean scores for the SF-MPQ was 0.553 (p = 0.47). At 12 months, the pain scores had decreased in both groups; the difference was 0.199 (p = 0.71). The number of breast operations or surgical complications did not correlate with breast pain in either group. Acute RT toxicity scores did not correlate with breast pain or QOL scores at 12 months. CONCLUSION: These results suggest that breast RT does not significantly contribute to breast pain or adversely impact the QOL up to 12 months after treatment in postmenopausal patients with node-negative breast cancer who take TAM.